Aspek Fundamental Teknikal dan Makroekonomi pada Sektor Energi di Bursa Efek Indonesia Periode 2015 – 2019 - Muhamad Bagas Prastio; Muhani; Irma Setyawati (Jurnal Kajian Ilmiah, 2022)
The purpose of this study is to analyze stock price using fundamental, technical and macroeconomic aspects. The research data was obtained from the Indonesia Stock Exchange for Energy Sector Companies, 2015 - 2019. Multiple regression equations were used to determine the effect between stock prices and fundamental, technical and macroeconomic aspects. Fundamental aspects include Earning Per Share, Return on Equity, Current Ratio and Debt to Equity Ratio. The technical aspect is seen from the trend of stock movements, while the macroeconomic aspect is shown by the interest rates ofr Bank Indonesia Certificates, world oil prices, and foreign exchange rates. The results of the study show that Earning Per Share and stock price movements have a positive and significant effect on stock prices, Return on Equity, Current Ratio, Debt to Equity Ratio, and the Rupiah Exchange rate have a negative and insignificant effect, while the interest rate ofr Bank Indonesia Certificates and world oil price have a negative and significant effect. From this research, it is hoped that it will be useful for academics and the public to pay attention to aspects that affect stock prices in investing in the shares of a company. Besides that, it can also be useful for companies in determining strategies to increase stock prices.